DEVELOPING ENGLISH TEXTBOOK MATERIALS FOR THE TENTH GRADE STUDENTS OF VOCATIONAL SCHOOL BY INCORPORATING COLLOCATION - Prisila Duana Intamanjana; Clarry Sada; Yohanes Gatot Sutapa Yuliana (Fakultas Keguruan dan Ilmu Pendidikan Universitas Tanjungpura, 2019)
The purpose of this research is to design and develop speaking and writing materials from “Bahasa Inggris” textbook for the tenth grade students of vocational school by incorporating collocation expressions and adding the explanations of those expressions which will be used into dialog texts for speaking and writing activities. The method of this study will be Design and Development Research. The development were needed due to the need for the students to learn natural English thus the participants of this research will be the tenth grade students of St. Monika Vocational School. Since this research will evaluate the usability and the practicality of the materials, the participants will be assigned to analyse the collocation expressions, the use of the expressions and the meanings of the collocations expressions contained in the dialogues. The feedback and responses from the participants are then gathered and analysed as the formative evaluation for the improvement of the materials.